Integration of Contemporary Islamic Education Management Models in Islamic Higher Education Institutions, An Evaluation of Implementation in the Modern Era - Zawaliyah, Syahida; Nugraha, Mulyawan Safwandy (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study investigates the application of contemporary Islamic education management models in Islamic Higher Education Institutions (PTKI) and evaluates their effectiveness in the context of modern education. It emphasizes how lecturers and students employ digital technologies, how students adjust to modern learning systems, and how Qur’anic values are integrated into teaching and learning processes. The findings indicate that the use of Learning Management Systems (LMS), Zoom, PowerPoint, and online assessments enhances teaching efficiency and educational management, while maintaining adherence to Islamic values. A literature review method was employed, drawing insights from journals, books, and recent research reports between 2015 and 2025. This approach provides a comprehensive understanding of digital integration in Islamic education management and its impact on student learning and character development.